Pattern and severity of injuries, risk factors and outcome of Road Traffic Accident victims attending emergency department of Birat Medical College Teaching Hospital - Gyawali, Sangya; Shah, Rajeev; Mandal, Nitesh (Birat Journal of Health Sciences, 2024)
Introduction: Road Traffic Accidents (RTA) is considered as one of the major public health problems around the globe. It is one of the top 5 causes of morbidity and mortality in South East Asia. Objectives: To find out pattern and severity of injuries, possible risk factors and outcome of victims of RTA attending emergency ward.Methodology: This is a cross-sectional study. All the patients with history of RTA attending the emergency ward have been enrolled with written informed consent after obtaining ethical clearance. Those patients with a history of sudden accidental fall or injury by falling objects were not included. The patients are assessed based on a semi standardized study proforma. The final outcome of the patient at the emergency department is noted.Result: Young adults (17-30 years) were injured most in Road traffic accident (38.41%) Most of them had head injury (59.8%) due to light vehicle (65.2%). Most accidents occurred during evening time (64.3%). Fewer of them were under the influence of alcohol (17%). 39% of the patients were severely injured. 3% patients expired at the emergency ward and 32% of the patients got admitted in ICU. Young adults were severely injured (53.8%) compared to older adults (33.33%). Conclusion: Young adults were involved most and major accidents were due to light vehicles. The majority of the patients had a milder form of injury requiring hospital admissions. The most common pattern was head injury. fewer of them were under alcohol influence.